Efecto de la adición de nopal (Opuntia ficus-indica) cocido a vapor a la dieta de lechones postdestete sobre citocinas proinflamatorias, integridad intestinal y desempeño productivo - Ponce de León Zavala, Aarón (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
The general objective was to evaluate the effect of the addition of O. ficus-indica (Ofi) on a fresh (BF) and steamed (St) basis to the diet of piglets in the weaning-initiation phase (6-25 kg) on proinflammatory cytokines, intestinal integrity (villi and intestinal bacteria) and productive performance and the particular objectives were: 1) to determine the expression of interleukin-1 beta (IL-1β), interleukin-12 (IL-12) and tumor necrosis factor-alpha (TNF-α); 2) evaluate the length (LVI) and width (WVI) of the intestinal villi, as well as the depth of the crypts of Lieberkühn (DCL) and crypt-to-villus ratio (C:V-R) of the small intestine; 3) evaluate the growth of gram-positive bacteria in the intestine; 4) determine serum glucose levels (GLU); 5) establish the voluntary consumption (VC) of commercial food (CF); 6) to compare the feed conversion (FC) between piglets added with nopal in BF and St. For the evaluation of the effect of the addition of Ofi to the diet of post-weaning piglets, 60 weaned piglets (6.9±1.1 kg) were used to form three groups (n=20 piglets/group) with two replications/group (n=10 piglets/repeat): Control group (G1), Group with Ofi in BF (G2) and Group with St Ofi (G3). The three groups received CF ad libitum according to their productive phase. The addition of Ofi in G2 and G3 to the diet was based on 1% of the piglet's average weight/week. The following were evaluated: VC of CF and Ofi (BF and St), piglet weight (PW), weight gain (WG), FC, GLU, LVI and WVI, DCL, C:V-R, gram-positive colony-forming units (CFU) in intestinal content and expression of IL-1β, IL-12 and TNF-α. The information collected was statistically analyzed through repeated measurements and the differences between groups by means of least squared means to a α = 0.05).

El objetivo general fue evaluar el efecto de la adición de O. ficus-indica en base fresca (BF) y cocida al vapor (CocV) a la dieta de lechones en la fase destete-destete-iniciación (6-25 kg) sobre citocinas proinflamatorias, integridad intestinal (vellosidades y bacterias intestinales) y desempeño productivo y los objetivos particulares fueron: 1) determinar la expresión de interleucina-1 beta (IL-1β), interleucina-12 (IL-12) y factor de necrosis tumoral-alfa (TNF-α); 2) evaluar el largo (LVI) y ancho (AVI) de las vellosidades intestinales, así como la profundidad de las criptas de Lieberkühn (PCL) y relación cripta/vellosidad (RCV) del intestino delgado; 3) evaluar el crecimiento de bacterias grampositivas en el intestino; 4) determinar los niveles séricos de glucosa (GLU); 5) establecer el consumo voluntario (CVol) de alimento comercial (AC); 6) comparar la conversión alimenticia (ICA) entre los lechones adicionados con nopal en BF y CocV. Para la evaluación del efecto de la adición de O. Ficus-indica a la dieta de lechones postdestete, se utilizaron 60 lechones destetados (6.9±1.1 kg) para formar tres grupos (n=20 lechones/grupo) con dos repeticiones/grupo (n=10 lechones/repetición): Grupo testigo (G1), Grupo con nopal en BF (G2) y Grupo con nopal CocV (G3). Los tres grupos recibieron AC ad libitum conforme su fase productiva. La adición de nopal en G2 y G3 a la dieta fue con base al 1% del peso promedio/semana del lechón. Se evaluó: CVol de AC y de nopal (BF y CocV), peso del lechón (PL), ganancia de peso (GP), ICA, GLU, LVI y AVI, PCL, RCV, unidades formadoras de colonias (UFC) grampositivas en contenido intestinal y expresión de IL-1β, IL-12 y TNF-α. La información recabada se analizó estadísticamente a través de mediciones repetidas y las diferencias entre grupo mediante medias de mínimos cuadrado a un α = 0.05).
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FQFB-M-2025-0338; Estrés; Alimentación; Salud intestinal; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19268